The Road to Abolition? : the Future of Capital Punishment in the United States. - Ogletree, Charles J. (Charles Hamilton Houston Institute Series on Race & Justice., 2009)
At the start of the twenty-first century, America is in the midst of a profound national reconsideration of the death penalty. There has been a dramatic decline in the number of people being sentenced to death as well as executed, exonerations have become common, and the number of states abolishing the death penalty is on the rise. The essays featured in The Road to Abolition? track this shift in attitudes toward capital punishment, and consider whether or not the death penalty will ever be abolished in America. The interdisciplinary group of experts gathered by Charles J. Ogletree Jr., and Au.